Me, the City - Lidin, Konstantin (project baikal, 2014)
The search for identity of cities looks rather urgent and attracts attention of many researchers. Addressing this issue, the article draws an analogy between a human person and a city. Like a city, a human being needs to comprehend his self-identity in order to resist depressive tendencies. It is shown that a person’s depressive symptoms are similar to those of cities. The city identity necessary to resist depression can be searched for both historically and geographically. The historical aspect consists of local myths and legends about the city and the citizens. The geographical aspect of identity comprises features of the terrain, climate, flora and fauna of the region where the city is located.
Keywords: identity of cities; depression; depressive territories; diagnostics; treatment; myths and legends about the city; scenery; landscape; cultural geography; social psychology